2017
DOI: 10.1038/s41523-017-0034-6
|View full text |Cite
|
Sign up to set email alerts
|

Clinical outcomes in patients with node-negative breast cancer treated based on the recurrence score results: evidence from a large prospectively designed registry

Abstract: The 21-gene Recurrence Score® (RS) assay is a validated prognostic/predictive tool in ER + early-stage breast cancer. However, clinical outcome data from prospective studies in RS ≥ 11 patients are lacking, as are relevant real-life clinical practice data. In this retrospective analysis of a prospectively designed registry, we evaluated treatments/clinical outcomes in patients undergoing RS-testing through Clalit Health Services. The analysis included N0 ER + HER2-negative breast cancer patients who were RS-te… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

13
69
0
1

Year Published

2018
2018
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 59 publications
(83 citation statements)
references
References 29 publications
13
69
0
1
Order By: Relevance
“…This appears to mirror results reported by Dowsett et al in the trans-ATAC evaluation of post-menopausal patients with N0 and N1 disease, in which confidence intervals overlapped for both groups of patients with RS 0-17 [13]. The lymph node negative population studied in TAILORx is consistent with the population evaluated in the SEER and Clalit registry studies with respect to age, tumor size, tumor grade, and RS distribution, suggesting a reasonable reflection of BC populations in their respective countries [26,27].…”
Section: Using the Assays To Guide Treatment Decisions In Clinical Prsupporting
confidence: 80%
See 1 more Smart Citation
“…This appears to mirror results reported by Dowsett et al in the trans-ATAC evaluation of post-menopausal patients with N0 and N1 disease, in which confidence intervals overlapped for both groups of patients with RS 0-17 [13]. The lymph node negative population studied in TAILORx is consistent with the population evaluated in the SEER and Clalit registry studies with respect to age, tumor size, tumor grade, and RS distribution, suggesting a reasonable reflection of BC populations in their respective countries [26,27].…”
Section: Using the Assays To Guide Treatment Decisions In Clinical Prsupporting
confidence: 80%
“…This all suggests that the 21 gene assay, by identifying a smaller high-risk population than other MGAs, may be more effective in reducing overtreatment without compromising outcome. The absence of CT benefit in the primary survival analysis of TAILORx patients with RS 0-25 suggests that CT might be spared in as many as 85% of node-negative, HER2-negative, ERþ BC patients, based on the proportion of such individuals in TAILORx [5,6], the SEER registry [26], the Clalit registry [27], and the global Genomic Health commercial database [28].…”
Section: Using the Assays To Guide Treatment Decisions In Clinical Prmentioning
confidence: 99%
“…In addition, patients included in the ROXANE study showed more aggressive biologic features as compared with other large population‐based registries including real‐life data on the use of the RS test. With regard to N0 stage, the rate of patients with grade 3 tumors was about 17% in two population registries, as compared with 49.3% in ROXANE, without relevant differences in T‐stage distribution . In the Surveillance, Epidemiology, and End Results (SEER) registry, N1 patients with grade 1 and 2 breast cancer were 29.0% and 54.8%, respectively, as compared with 9.1% and 73.7% in the ROXANE study.…”
Section: Discussionmentioning
confidence: 97%
“…The identification of patients with high clinical risk and low genomic score with at least a 92.5% chance of being free of distant metastasis without chemotherapy at 5 years was demonstrated using the Mammaprint assay in the MINDACT trial . Prospective outcomes in >60,000 patients (including both clinical and epidemiological data) treated based on 21‐gene assay results have shown that patients within the low RS group (RS < 18) have excellent outcomes without chemotherapy . The prognostic power of the RS was validated in an endocrine‐treated NSABP B14 cohort, in the Kaiser Permanante, JBCRG, SWOG 8814 and in the transATAC studies .…”
Section: Introductionmentioning
confidence: 99%
“…21 Prospective outcomes in >60,000 patients (including both clinical and epidemiological data) treated based on 21-gene assay results have shown that patients within the low RS group (RS < 18) have excellent outcomes without chemotherapy. [32][33][34][35][36][37][38] The prognostic power of the RS was validated in an endocrine-treated NSABP B14 cohort, in the Kaiser Permanante, JBCRG, SWOG 8814 and in the trans-ATAC studies. 2,9,11,23,24,39 The predictive power of RS for the prediction of chemotherapy benefit was initially validated in the NSABP B20 study in endocrine only vs. chemoendocrinetreated cohorts.…”
Section: Introductionmentioning
confidence: 99%